Characteristics of Mengger Formation's volcaniclastic in Cisaat River, Brebes, Central Java, Indonesia. Issue 1 (1st August 2022) - Aini, H N; Setiawan, N I; Haq, M N; Mahardika, C A; Nugroho, S; Setiawan, R
Abstract: The Cisaat River in Brebes Regency, Central Java, is one of the sites on Java Island where vertebrate fossils were found. Mengger Formation, composed of volcaniclastics material such as tuff and pumice fragments, contains these fossils. The presence of vertebrate fossils along with volcanic deposits has remained unclear of its deposition history. This research characterizes the volcaniclastic rocks in Mengger Formation based on geological field observation and petrography analysis. The study aims to identify and distinguish its primary and secondary volcaniclastic depositional processes. The measured stratigraphic sections reveal that the formation has 7 lithofacies from older to younger, namely grain-supported conglomerate, sandstone, siltstone, sandy mudstone, matrix-supported conglomerate, tuffaceous sandstone, and tuffaceous conglomerate. The primary volcaniclastic materials comprise pumice clast, plagioclase, pyroxene, hornblende, quartz, biotite, lithic fragments, and volcanic glass. In contrast, secondary volcaniclastic or epiclastic-sedimentary materials contain lithic fragments, quartz, plagioclase, pumice clast, and clay matrix. The origin of the resedimented volcaniclastic material was probably derived from a large volume of ignimbrite near the volcano. From the deposit and measurement section, it can be concluded that the type of the Mengger volcaniclastic.